Civics teachers and student awareness of money politics: A case study in Meukek, South Aceh - Nuralisa, Akma Rita; Yusuf, Rusli; Maimun (International Journal of Advances in Educational Research, 2025)
Money politics poses a serious threat to the quality of democracy by undermining electoral integrity and discouraging meaningful political participation. Civics (PPKn) education plays a strategic role in fostering students’ political awareness and encouraging them to reject unethical political practices. This qualitative descriptive study involved 5 PPKn teachers and 8 high school students in Meukek District, South Aceh. Data were collected through interviews and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that PPKn teachers play a crucial role in curricular, co-curricular, and extracurricular activities. In curricular settings, they strengthen students’ understanding of the negative impacts of money politics through subject content and critical discussions. In extracurricular contexts, they promote student involvement in election simulations and political awareness campaigns. However, most schools in Meukek lack extracurricular programs focused on political education. Inhibiting factors include limited student interest in politics, economic constraints, cultural influences, low political literacy, and the pervasive culture of transactional politics. Enhancing the role of PPKn teachers across educational dimensions is essential to developing politically aware, critical-minded students who support clean and fair democratic practices.